ANALISIS STRATEGI PROMOSI BANK SYARIAH MANDIRI UNTUK MENINGKATKAN PENJUALAN - Laini, Rus (Mu'amalatuna: Jurnal Ekonomi Syariah, 2019)
In such thigh competition, information plays an important role to attract customers or services provided by the bank. The information itself is not always in the from of promotion, but also information of any form delivered by every stakeholder related to banking business. Seeing the advantages, opportunities, prospects and acceleration of the development of Islamic banking above, we need an effective communication as a promotional tool to the community in maximizing income. This research is a type of field research, qualitative descriptive that is describing and describing the state of an object and then analyze it. The data source was obtained from primary data and secondary data, with data collection techniques through interviews with leaders and practitioners of banking and through questionnaire 100 (one hundred) respondents. From the analysis it was found that the promotion carried out by Bank Syariah Mandiri (BSM) uses all the promotion mix (Advertising, personal selling, sales promotion, publicity) not yet oriented to the long term, but rather to the short term emphasis, therefore a promotion strategy is needed to further increase is by personal selling with the approach and education to the community